Technical Assistance in the Development of Public Service Standard Operating Procedures (SOPs) for Pejeng Village, Gianyar Regency - Ni Kadek Ayu Wirantini; I Nengah Merta; Ni Nengah Karuniati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
High-quality public services are a key indicator of effective village governance. However, the Government of Pejeng Village, Gianyar Regency, continues to face challenges due to the absence of well-documented and systematic Standard Operating Procedures (SOPs) for public service delivery. Consequently, service provision largely depends on individual practices of village officials, leading to inconsistencies, limited transparency, and uncertainty in service procedures. This community service program aimed to enhance the capacity of village officials in developing public service SOPs while producing a practical SOP document to serve as an official guideline for delivering public services. The program employed a participatory, educational, and collaborative approach, consisting of coordination, service identification, service flow mapping, socialization, training, technical assistance in SOP development, validation, and evaluation. Throughout the process, village officials actively participated as the primary partners to ensure that the resulting SOP reflected the actual needs and operational context of the village administration. The outcomes demonstrated an improvement in officials’ understanding of public service principles and SOP development techniques, the successful preparation of a comprehensive public service SOP document covering service workflows, administrative requirements, service standards, and processing times, as well as a stronger commitment among village officials to deliver services that are more effective, transparent, accountable, and citizen-oriented. This program is expected to serve as a best-practice model for strengthening public service governance that can be replicated by other villages in supporting bureaucratic reform and improving the quality of village public services.